As categorias de Aristóteles e suas categorias - Igor Mota Morici (2008)
This dissertation is meant to analyze the notion of category as it appears in Aristotles Categories. Despite its importance to his thought, Aristotle has never defined it. Consequently since later Antiquity it has been open to widely different interpretations. This study aims at elucidating what Aristotle understands categories to be and what role they are supposed to play in Categories through an examination of those interpretations and the text itself. In particular, we shall put forward the hypothesis that the Aristotelian notion of predication falls under the category of relation whose relata are the various categories. Thus, we intend to answer the questions we raised by providing an interpretative key based on that hypothesis.